REFLEKSI DALAM MEMAKNAI EKSISTENSI RAKYAT; ANTARA PEMILIHAN PRESIDEN DAN PEMILIHAN MPR - Efriza Efriza (Prima Center Indonesia, 2018)
This paper attempts to re-unravel the results of the 1945 amendment in analyzing the development and division in Indonesia, highlighting democracy and the people between the President's choice directly with the President's choice through the MPR, and addressing the 1945 Constitution amendment as the basis of the spirit of constitutional democracy in Indonesia. The results of this study clearly explain that democracy in Indonesia is more favorable based on the results of the 1945 Amendment and the Presidential Election directly and better and as part of the implementation of constitutional democracy in a more comprehensive manner.Keywords: Voters, Political Parties, Presidential Election, MPR and Constitutional Democracy